Fumigant dazomet induces tobacco plant growth via changing the rhizosphere microbial community - Xiao, Qingli; Dai, YuHao; Yu, Xi; Wang, Kai; Zhu, Xiaowei; Qin, Pingwei; Wang, Zhenzhen; Yuan, Ming; Peng, Kui; Wang, Jianlin; Tan, Qizhong; Yang, Liang; et al. (Scientific reports, 2025)
After continuous cropping for many years, crops are often subject to growth inhibition, which seriously affects their yields.In agricultural production, soil fumigation can effectively alleviate the biological stress on plants. However, the relationship between the microbial groups that respond to soil fumigation changes and plants, as well as whether their existence makes a beneficial contribution to plants, remains unclear. We explored the mechanism of soil fumigation promoting plant growth by affecting microorganisms. The results showed that dazomet treatment significantly alleviated the growth retardation of tobacco, and this difference was most obvious in the flourishing period of tobacco, when the plant height and leaf area increased by 3.33 times and 3.24 times respectively. In addition, the growth advantage of the above-ground tissue was significantly correlated with the root advantage ( P < 0.05). At the same time, we found that dazomet treatment significantly increased a large number of microbial groups positively related to roots, such as g_Pedobacter , g_Microbacterium and g_Brevundimonas . The results of structural equation modeling indicated that the microbial community, which was positively correlated with the amount of dazomet applied and also positively correlated with roots ( P < 0.05), was an important factor contributing to the growth advantage of tobacco. Overall, the findings of this study are of great significance for enhancing our understanding of soil remediation by fumigation and may have far reaching implications for the practical application of dazomet fumigation.